2010
DOI: 10.1097/00007890-201007272-01093
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Preservation by Machine Perfusion on Postoperative Outcome of Kidneys From Controlled Donors After Cardiac Death

Abstract: Introduction: Cumulative retrospective evidence suggests that preservation by hypothermic machine perfusion (HMP) reduces the incidence of delayed graft function (DGF) in kidney transplants from donors after cardiac death (DCD). However, two contemporary randomised clinical trials designed to evaluate the effect of MP in DCD kidney transplantation have shown contradictory results. Methods: To address whether HMP has a beneficial effect on the outcome of kidneys from controlled DCD, a comparative analysis betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Twenty-two studies [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] identified by the systematic search were included into the analysis (Table 2); fifteen were published papers and seven were abstracts. Ten were RCTs [6,11,12,15,16,18,19,21,24,25], seven studies were retrospective [7,8,9,10,17,22,23], and five were prospective [13,14,20,26,27]. Predominantly, the studies used a LifePort ® kidney transporter for hypothermic machine preservation; there was a large variation in cold storage solution type, with some studies not mentioning the specific cold storage preservation solution, but instead referring to local guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two studies [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] identified by the systematic search were included into the analysis (Table 2); fifteen were published papers and seven were abstracts. Ten were RCTs [6,11,12,15,16,18,19,21,24,25], seven studies were retrospective [7,8,9,10,17,22,23], and five were prospective [13,14,20,26,27]. Predominantly, the studies used a LifePort ® kidney transporter for hypothermic machine preservation; there was a large variation in cold storage solution type, with some studies not mentioning the specific cold storage preservation solution, but instead referring to local guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] comparing HMP and SCS described the incidence of DGF (Figure 3), and its duration (Figure 4), with a total of 7963 patients. The overall OR was 0.57 (0.45, 0.72, 95% CI), with p < 0.00001, favouring a statistically significantly lower prevalence of DGF in kidneys preserved by HMP.…”
Section: Resultsmentioning
confidence: 99%